FAKTOR – FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG PADA PERUSAHAAN INDUSTRI PLASTIK DAN KEMASAN YANG TERDAFTAR DI BEI PERIODE 2013 – 2018 - Endang Susilowati; Yuli Chomsatu S; Suhendro Suhendro (Jurnal Ilmiah Manajemen Ubhara, 2020)
The purpose of this research is to test the impact of the size of the KAP, the financial ratio (debt equity ratio, current ratio), 2018 2013 The audit opinion and the company. The study used 11 plastics and packaging industry companies listed on the IDX period 2013-2018. Simultaneous testing results show that the debt equity ratio, current ratio, size of the HOOD, audit opinions and company size together have the same effect on the audit report lag. The results of the hypothesis test showed that the current ratio and size of the KAP affect the audit report lag, while the results of the debt equity ratio hypothesis test, audit opinions and company size have no influence on the audit report lag Plastic and packaging industry companies.Keywords: Size Public Accountant Office, Financial Ratios, Audit Opinions, Company Size and Audit Report Lag